Hubung kait antara amalan perancangan strategik sistem maklumat (PSSM) dan prestasi agensi kerajaan di Malaysia: Kesan penyederhana konteks PSSM dan pendekatan PSSM - Hisyam, Harun (2016)
Strategic information system planning (SISP) as a management practice and process helps organizations to identify as well as selecting suitable computer- based systems for improving their organizational performance. Although, as an area of study, SISP has gained much attention among academics and practitioners, research that focuses on SISP in government agencies has not been emphasized. Given the limited number of studies on SISP in government agencies, this study initiated an attempt to investigate SISP among government agencies in Malaysia. The objectives of this study were to determine the relationship between SISP practices and performance of government agencies as well as to determine whether SISP contexts and SISP approaches moderate the relationship between SISP practices and performance of government agencies. More specifically, the study adopted the contingency framework to examine the moderating effects of SISP contexts and SISP approaches on the relationship between SISP practices and performance of government agencies in Malaysia. Questionnaires were sent to 254 government agencies that were registered with the Malaysian Administrative Modernization and Management Planning Unit (MAMPU). Descriptive analysis, Pearson correlation, and multiple and hierarchical regressions were used to analyze the data. Based on the analyses of the data obtained from the respondents, the results of the study indicated positive relationships between SISP practices and performance of the government agencies. Furthermore, the results also showed that SISP contexts and SISP approaches moderate the relationship between SISP practices and performance of the government agencies. The findings of this study appear to support the notion that SISP practices are related to the performance of government agencies. The association between SISP practices and the performance of government agencies as well as the moderating effects of SISP contexts and SISP approaches further suggests implications to practitioners, policy - makers and government agencies